Ego-Network Stability and Innovation in Alliances - Kumar, Pankaj; Zaheer, Akbar (Academy of Management Journal, 2019)
Much research has shown that firms’ ego network configurations—i.e., structural holes or network closure—help them achieve superior innovation outcomes. However, little is known about how the stability of the firm’s ego-network composition affects the firm’s innovation. In this paper, we investigate the outcomes of ego-network stability in an alliance context, arguing that stability actually reduces innovation for the focal firm. We further investigate two contingencies—namely, the structural holes the focal firm spans and the geographic concentration of its inventive activities—that moderate the detrimental innovation effects of ego network stability. Focal firms can limit the negative effects of ego-network stability on innovation by spanning structural holes in their alliance portfolios, whereas the negative effects are worsened when the focal firms’ inventive activities are geographically concentrated in a single country. We empirically test our hypotheses using 198 biopharmaceutical firms headquartered in the United States over a 21-year period from 1985 to 2005. Our results support our predictions.